Сhronic relapsing inflammatory optic neuropathy: diagnostic strategies and treatment (literature review) - T.I. Nehrych; M.B. Kopchak; S.Ya. Kyryliuk (Medičnì Perspektivi)
The article presents a review and analysis of scientific works on the problem of chronic relapsing inflammatory optic neuropathy, its diagnostic criteria and treatment methods. Chronic relapsing inflammatory optic neuropathy, first described in 2003, is an autoimmune inflammatory disease of the optic nerve of unknown etiology, accompanied by frequent painful episodes of optic neuritis, with a clear response to steroid therapy and relapses after its withdrawal. An analysis of foreign works published in the E-Library, CrossRef, PubMed, Web of Science, Scopus databases was carried out in order to systematize data on the etiology, pathogenesis, clinical manifestations, diagnostic criteria, differential diagnosis and treatment of this pathological condition. It has been established that chronic recurrent inflammatory optic neuropathy is a rare, recurrent, corticosteroid-dependent optic neuropathy in which there is no other neurological deficit, no etiological factor is identified and it is a diagnosis of exclusion. It is important to identify such patients because the appointment of appropriate immunosuppressive therapy causes remission of the disease.